The Relationship Between Parental Socio-Economic Status, Birthweight, and Development in Children Aged 1-5 Years in Surakarta - Kusumasari, Rizka Agnes; Tamtomo, Didik; Retno Dewi, Yulia Lanti (Journal of Maternal and Child Health, 2016)
Background:ÃÂ Health report by The Ministry of Health in 2006 revealed that 16% of children under five had mild to severe development problem.ÃÂ  About 5-10% of children under five had mental retardation. The current study hypotesized that parental socio-economic status such as family income and maternal education affect child development. The purpose of this study was to analyze the relationshipbetween parental socio-economic status, birthweight, and development in children aged 1-5 years in Surakarta.Subjects and Method:ÃÂ This was an analytic observational study with case control design. This study was conducted at Ngoresan Health Center, Surakarta, from December, 2016 to January, 2017. The study population was children under five living within the area of Ngoresan Health Center. A total of 100 children under five was selected by fixed disease sampling, consisting of 25 cases and 75 controls. The dependent variable was child development, measured by Ministry of HealthÃ¢â¬â¢s KPSP. The independent variables were family income, maternal education, and birthweight. The data were analyzed by chi-square and multiple logistic regression.Results:T here were positive and statistically signifcant relationships between maternal education Ã¢â°Â¥ high schoolÃÂ  (OR=1.61; 95% CI=1.5 to 15.7; p=0.046), family income Ã¢â°Â¥minimum regional wage(OR=5.1; 95% CI= 1.1 to 22.8; p=0.032), and normal birthweight (OR=8.5; 95% CI= 2.4 to 30.1; p=0.001) and child development.Conclusion:ÃÂ There are positiverelationships between highfamily income,high maternal education, normal birthweight, and normal development in children aged 1-5 years.Keywords:ÃÂ parental socio-economic status, birthweight, child developmentÃÂ Correspondence:ÃÂ Rizka Agnes Kusumasari. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: rizka.agnes@gmail.comJournal of Maternal and Child Health (2016), 1(3): 195-199https://doi.org/10.26911/thejmch.2016.01.03.07ÃÂ